An overview study on the educational psychological assessment by measuring students' stress levels - Kosherbayeva, A. N.; Issaliyeva, S.; Begimbetova, G. A.; Kassymova, Dr. Gulzhaina K.; Kosherbayev, R.; Kalimoldayeva, A. K. (LPMPP Universitas Negeri Yogyakarta, 2024)
This article reviews the literature on the field of bibliographic analysis of the literature on educational assessment, psychological stress during the examination period, human memory, stress in the classroom, psychometric tools, and measurement scales for students' stress. It examined the link between students' social and psychological health, stress levels, and preferred social support systems. The research subjects were Abai Kazakh National Pedagogical University first-year students (n=299) who completed the Perceived Stress Scale and a Likert rating-type scale via a Google form. The validity and reliability of the scale were respectively confirmed through